Artificial spider silk supports and guides neurite extension in vitro. Issue 11 (11th October 2021) - Hansson, Magnus L.; Chatterjee, Urmimala; Francis, Juanita; Arndt, Tina; Broman, Christian; Johansson, Jan; Sköld, Mattias K.; Rising, Anna
Abstract: Surgical intervention with the use of autografts is considered the gold standard to treat peripheral nerve injuries. However, a biomaterial that supports and guides nerve growth would be an attractive alternative to overcome problems with limited availability, morbidity at the site of harvest, and nerve mismatches related to autografts. Native spider silk is a promising material for construction of nerve guidance conduit (NGC), as it enables regeneration of cm‐long nerve injuries in sheep, but regulatory requirements for medical devices demand synthetic materials. Here, we use a recombinant spider silk protein (NT2RepCT) and a functionalized variant carrying a peptide derived from vitronectin (VN‐NT2RepCT) as substrates for nerve growth support and neurite extension, using a dorsal root ganglion cell line, ND7/23. Two‐dimensional coatings were benchmarked against poly‐d ‐lysine and recombinant laminins. Both spider silk coatings performed as the control substrates with regards to proliferation, survival, and neurite growth. Furthermore, NT2RepCT and VN‐NT2RepCT spun into continuous fibers in a biomimetic spinning set‐up support cell survival, neurite growth, and guidance to an even larger extent than native spider silk. Thus, artificial spider silk is a promising biomaterial for development of NGCs.